Carbon‐centered radical initiators for polymerization of unsaturated monomers: Modeling and reactivity studies. (9th November 2018) - Keaton, Richard; Froese, Robert D.; Ewart, Sean; Spencer, Liam; Pearson, David; Busch, Markus; Bauer, Christian
Abstract : A series of sterically encumbered diphenylethane molecules was examined to understand their fundamental ability to undergo homolytic bond cleavage and initiate radical polymerization of unsaturated monomers. The structures computed by density functional theory (DFT) showed a relationship between increasing C‐C bond length of the ground state molecule and reduced bond dissociation energy (BDE). The computed activation barriers associated with radical addition to acrylate were relatively low indicating that once radicals were formed, initiation of polymerization would be facile. Good correlations between computed BDE and experimentally‐determined onset temperatures for acrylate polymerization were found. The Molecule (13) with the lowest BDE (33.8 kcal/mol) determined in this work had an onset temperature of 85 °C. Ethylene polymerization failed to show a similar trend as molecules possessing the weakest C‐C bonds did not effectively initiate ethylene polymerization. Theoretical calculations demonstrated a trend in which the molecules with the lowest BDEs had the highest barriers for addition of ethylene. These barriers were significantly higher than standard peroxide initiation or chain propagation. Upon ramping the temperature, it is postulated that molecules with low BDE values form radicals but do not have sufficient energy to add to ethylene before succumbing to detrimental side‐reactions. POLYM. ENG. SCI., 59:E52–E58, 2019. © 2018 Society of Plastics Engineers